Shift of Trend of Research Topic of Global Halal Food and Blockchain And Where They Are The Most Popular - Nanang Qosim (Universitas Airlangga, 2022)
The halal food market is growing rapidly. Blockchain is the tracing system that allows the data of halal commodities to be saved and accessed safely by industries. This study has the purpose of analyzing the most frequently used words in previous studies that discussed the usage of blockchain in halal food. This study used bibliometrics in collecting and analyzing metadata from Scopus and the Web of Science websites. There were 23 documents found in Scopus and 13 documents from the Web of Science from 2019–2023. The result showed that the word traceability was frequently used inside the author's keyword, title, and abstract of papers that were included in Scopus and the Web of Science databases. Keywords: Blockchain, halal, food, traceability